2007
DOI: 10.1094/pdis-91-7-0905b
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Anthracnose Caused by Elsinoe ampelina on Muscadine Grapes (Vitis rotundifolia) in Northern Florida

Abstract: Anthracnose of grapes is an economically devastating disease caused by Elsinoe ampelina (2). Warm, humid weather favors disease development, and therefore in the United States, it is generally restricted to grape-growing areas east of the Rocky Mountains. Vitis vinifera is highly susceptible to the disease, which is one of the principal factors preventing the development of an industry with this high-quality grape in the southeastern United States. Growers in this area produce local species-such as muscadine g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In previous studies, morphological features were used partially to characterize E. ampelina (Poolsawat et al., ; Schilder et al., ; Sompong et al., ; Yun et al., ). In this study, cultural and conidial features from Brazilian and Australian isolates also offered substantial information to support the species identification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, morphological features were used partially to characterize E. ampelina (Poolsawat et al., ; Schilder et al., ; Sompong et al., ; Yun et al., ). In this study, cultural and conidial features from Brazilian and Australian isolates also offered substantial information to support the species identification.…”
Section: Discussionmentioning
confidence: 99%
“…Grape species such as Vitis labrusca, V. vinifera, V. rotundifolia, V. riparia and Vitis sp. (hybrids) are susceptible to anthracnose (Barros et al, 2015;Kono, Sato, Ban, & Mitani, 2013;Louime et al, 2011;Yun, Louime, & Lu, 2007). Generally, table grape cultivars are more susceptible to anthracnose than wine grape cultivars (Hart, Magarey, Emmett, & Magarey, 1993;Kono et al, 2013).…”
mentioning
confidence: 99%
“…The genomic DNA of E. ampelina isolates YL-1 was extracted using the CTAB method (Möller, Bahnweg, Sandermann, & Geiger, 1992). The ITS region was amplified using the forward primer (5′-TCCGTAGGTGAACCTGCGGA-3′) and reverse primer (5′-TCCTACCTGATCCGAGGTCA-3′) described by Yun, Louime, and Lu (2007). PCR reaction was carried out in a final volume of 20 μl composed of TaKaRa Ex Taq (5U μl −1 ), 10 × Ex Taq buffer, 0.2 μM dNTPs, 0.2 μM primers, and 100 ng template DNA.…”
Section: Dna Extraction Amplification and Phylogenetic Analysismentioning
confidence: 99%
“…However, bacterial, fungal and viral pathogen diseases, such as powdery mildew (Erysiphe necator), downy mildew (Plasmopara viticola), Botrytis cinerea, and anthracnose (Elsinoe ampelina) are major limiting factors in grapevine production and quality. E. ampelina is a biotrophic fungus originating in European grapes that can cause devastating disease in most of the world's grape producing areas, but especially in areas with high rainfall [1,2]. The pathogen attacks all young parts of the grapevine, such as leaves, tendrils, fruits and petioles.…”
Section: Introductionmentioning
confidence: 99%
“…As the disease progresses, the symptoms usually appear as numerous circular spots, which enlarge and become sunken, resulting in lesions with round edges [1]. High temperatures and humidity are known to contribute to occurrence of the disease and associated fungal growth [2]. The breeding of grape cultivars that are resistant to anthracnose is an important objective, and previous studies have shown that while European V. vinifera cultivars are highly susceptible, American grapes and Vitis hybrids exhibit varying levels of resistance [3].…”
Section: Introductionmentioning
confidence: 99%